Exploring the decolonisation of the Environmental Management Curriculum in a Rural Historically Disadvantaged Institution of Higher Education - Moyo, Inocent (School of Education, 2025)
In the Global South generally and South Africa specifically, calls for decolonising the university curriculum have gained momentum in the recent past. In South Africa, this was aptly demonstrated by the 2015/2016 #FeesMustFall protests which called for inter alia, a transformed university and its curriculum. This has led to calls for the decolonisation of academic disciplines like Geography, among others. Against this backdrop, this study analyses the decolonisation of the Environmental Management curriculum in a rural historically disadvantaged institution of higher education. The specific objectives are to (a) identify the basis of knowledge that constitutes the current Environmental Management curriculum in the discipline of Geography in a rural HDI using the curriculum document and the interview inputs/perceptions from academics and students, (b) assess the limitations and/or problems of the current Environmental Management curriculum using the notions of biography and geography of knowledge and (c) explore pedagogic approaches to recentre the biography and geography of knowledge in the current Environmental Management curriculum. To achieve these, a qualitative study was utilised in terms of in-depth interviews with two academic staff members and ten fourth-level (Honours) students who taught and studied this module in question, respectively. The findings suggest that the content, knowledge, and pedagogy in the Environmental Management curriculum under consideration is Eurocentric because it excludes IKS. In addition, the study findings suggest that both academics and students have identified gaps and/or limitations in the current Environmental Management curriculum because its locus of enunciation is not Africa and South Africa. This is the context within which the respondents in the study have suggested the need to include IKS which could contribute to epistemic access, epistemic presence, epistemic freedom as well as cognitive justice. All this suggests that a decolonised Environmental Management curriculum should include IKS as an integral component. In terms of pedagogy, the practical element must be emphasised together with the introduction of IKS holders into the learning spaces. By extension, assessment should address existing environmental problems in the settings where students and community members live. The suggested assessment approaches include action research. The proposed Environmental Management curriculum must not be alienated and alienating. It must be about the production of knowledge for life.